Albania : 2011 Article IV Consultation: Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Albania. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The global crisis left Albania fairly unscathed and ushered in the needed economic rebalancing. The policy framework has been challenged in the post-crisis environment significant headwinds. Despite improvement, external imbalances remain elevated. Fiscal consolidation in terms of a more realistic macroeconomic framework will require credible measures and sustained efforts. Financial sector supervision and regulation will need to stay ahead of evolving challenges. Boosting productivity by attracting foreign investment is essential for higher sustainable growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet